The expression status of human epidermal growth factor receptor 2 in epithelial ovarian cancer in Ibadan, Nigeria (2016)
It has been proposed that the overexpression of the human epidermal growth factor receptor 2 (HER2/neu proto oncogene) could be a possible therapeutic target in epithelial ovarian cancer, as has been the case in breast carcinomas. However, there is lack of knowledge on the status of the gene in neoplasms which occur in black women. The objective of this study was to determine HER2/neu expression status in EOC in black women. Method: Ninety cases of EOC were evaluated for HER2/neu protein expression using immunohistochemistry. Results: HER-2/neu expression was observed in 33 of the 90 cases (37%), of which 15 EOC cases (17%) were weakly or moderately positive, and 18 (20%) strongly positive. A significant association was not found between HER-2/neu expression and age, International Federation of Gynecologists and Obstetrics (FIGO) stage, grading and histological subtypes (p-values of 0.463, 0.360, 0.975 and 0.168, respectively). However, there were more cases of advanced stage disease (III/IV) with HER-2 expression than early-stage EOC (I/II). In this study, 21%, 36% and 42% of HER2/neu-positive tumours were grades 1, 2 and 3, respectively. A higher proportion of serous carcinomas (as opposed to mucinous carcinomas) was also observed to be HER2/neu positive. Conclusion: HER2/neu expression was observed to increase with advanced stages of cancer, and was more commonly seen in serous, rather than in mucinous, carcinomas.